Education Research: reflections on the discursive perspective (Olhar de Professor, 2024)
The purpose of this article is to discuss how we have used certain notions of a theoretical approach chosen to enlighten the objects of a research carried out during a Master's research in the area of Education. The main source for our work - carried out in dialogue with such theory - was the Portuguese translation of the book by Ernesto Laclau and Chantal Mouffe entitled Hegemony and Socialist Strategy. This article presents some of the theoretical and strategic choices made during the aforementioned research work. Such choices follow the discursive field of a political theory, a theory about 'the' political: Laclau and Mouffe's Theory of Discourse. This study aims to highlight that fact that the focus given in the analysis of the discursivities/disputes on screen – our research objects – allowed us to find ways of exploring notions of the referred post-structuralist theory such as political space, articulation, demand, nodal point and hegemony.
Keywords: Research; Education.; Political Approach.